Comparative Evaluation of the Disintegrant Properties of Starches from Three Cultivars of Dioscorea rotundata (Poir) (2022)
Dioscorea rotundata Poir starches from three cultivars (Lagos, Giwa, and Sule) were evaluated as exo-disintegrants (5 and 10%w/w) in paracetamol tablet formulations to determine whether the similarity in their physicochemical and material properties translates to performance in tablet formulation. The tablets were prepared by wet granulation and were evaluated for compressional properties (Heckel equation), mechanical strength (crushing strength and friability), and drug release (disintegration and dissolution times). Plastic deformation occurred in all tablets with rank order for the onset of plastic deformation Lagos>Giwa>Sule. An increase in the concentration of disintegrants in the tablets led to a decrease in mean yield pressure, total relative precompression density, and relative density at low pressure, but an increase in relative density at zero pressure. The crushing strength and disintegration times of the tablets were dependent on the disintegrants' concentration. All tablets passed the disintegration test (≤15min) with tablets containing the Sule cultivar producing the fastest disintegration (p<0.05). Tablets containing 10% of the Sule cultivar had the fastest release of paracetamol (t80=32.1min), though it failed the compendial standard for immediate release tablets (t80≤30min). Starches from the three cultivars despite their similar physicochemical and material properties exhibited different disintegrant properties and could find different applications as excipients in tablet formulations.